Factores familiares que inciden en el riesgo de consumo de sustancias psicoactivas en adolescentes del barrio 31 de Octubre de Riohacha, La Guajira. (2023)
The purpose of this study was to identify the relationship between family factors with the risk of consumption of psychoactive substances in adolescents from the 31 de Octubre neighborhood of Riohacha, La Guajira. For this, a descriptive methodology was used, with a quantitative approach, the authors worked with a sample of 6 adolescents between the ages of 14 and 18 who currently reside in the 31 de Octubre neighborhood of Riohacha-La Guajira. , in relation to the instruments applied by the authors of this study were the family APGAR scale devised by Smilkstein (1978) to evaluate the functioning of the family system (Arias and Herrera, 1994) to identify families at risk and on the other hand, it was applied the CRAFFT questionnaire developed by psychiatrists (Knight and Sherit) at Children's Hospital Boston, MA, which consists of six questions and assesses the prevalence of psychotropic substances or the risk of substance abuse. It was found that there is a significant low negative correlation with experimental consumption, as well as with the dimensions of recreational consumption and dependence or abuse of consumption, in the Dependence or abuse of consumption only a low significant correlation was found in the dimension of family functioning related to the Cooperation.